2010
DOI: 10.1002/etc.165
|View full text |Cite|
|
Sign up to set email alerts
|

Polyhalogenated aromatic hydrocarbons and metabolites: Relation to circulating thyroid hormone and retinol in nestling bald eagles (Haliaeetus leucocephalus)

Abstract: Polyhalogenated aromatic hydrocarbons are global contaminants that are often considered to be endocrine disruptors and include 1,1-dichloro-2,2-bis(4-chlorophenyl)ethylene (p,p'-DDE), polychlorinated biphenyls (PCBs), and polybrominated diphenyl ethers (PBDEs). The present study examined these compounds and their hydroxylated metabolites or analogues and relationships with circulating thyroid hormones and retinols in plasma from nestling and adult bald eagles in British Columbia, Canada, and California, USA. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 73 publications
2
19
1
Order By: Relevance
“…However, although Ellis-Hutchings et al (2006) also observed a significant decrease in vitamin A liver content in DE-71 exposed rats during gestation and lactation, no change in circulating retinol could be detected, suggesting that the mobilisation of vitamin A from the liver was not enhanced. Similarly, no significant correlation between SPBDEs and retinol in blood plasma were found in bald eagles with levels of contamination 10 times higher than the grey seals of the present study (Cesh et al, 2010). On the other hand, American kestrels (Falco sparverius) exposed to environmentally relevant PBDE congener concentrations had lower plasma retinol levels when exposed to BDE-99 and -100, while reduced hepatic retinol and retinyl palmitate concentrations were observed when kestrels were exposed to BDE-47 (Fernie et al, 2005).…”
Section: Relationships Between Pbdes Meo-pbdes and Vitamin Acontrasting
confidence: 77%
See 4 more Smart Citations
“…However, although Ellis-Hutchings et al (2006) also observed a significant decrease in vitamin A liver content in DE-71 exposed rats during gestation and lactation, no change in circulating retinol could be detected, suggesting that the mobilisation of vitamin A from the liver was not enhanced. Similarly, no significant correlation between SPBDEs and retinol in blood plasma were found in bald eagles with levels of contamination 10 times higher than the grey seals of the present study (Cesh et al, 2010). On the other hand, American kestrels (Falco sparverius) exposed to environmentally relevant PBDE congener concentrations had lower plasma retinol levels when exposed to BDE-99 and -100, while reduced hepatic retinol and retinyl palmitate concentrations were observed when kestrels were exposed to BDE-47 (Fernie et al, 2005).…”
Section: Relationships Between Pbdes Meo-pbdes and Vitamin Acontrasting
confidence: 77%
“…Gabrielsen et al, 2011 reported negative relationships between several HO-PCBs and thyroid hormones in in vivo studies with hooded seals (Cystophora cristata). Similarly, although not demonstrated in wild mammals yet, Cesh et al (2010) found negative correlations between HO-PCBs and retinol in plasma of nestling bald eagle (Haliaeetus leucocephalus). These observations favour a competitive binding of HO-PCBs to TTR in wild animals.…”
Section: Relationships Between Pcbs Ho-pcbs and Vitamin Amentioning
confidence: 78%
See 3 more Smart Citations